Clinical trial of oral nelfinavir before and during radiation therapy for advanced rectal cancer - Hill, Esme J.; Roberts, Corran; Franklin, Jamie M.; Enescu, Monica; West, Nicholas; Macgregor, Thomas P.; Chu, Kwun-Ye; Boyle, Lucy; Blesing, Claire; Wang, Lai-Mun; Mukherjee, Somnath; Anderson, Ewan M.; et al. (Clinical Cancer Research, 2016)
Purpose: Nelfinavir, a PI3K pathway inhibitor, is a radiosensitizer that increases tumor blood flow in preclinical models. We conducted an early-phase study to demonstrate the safety of nelfinavir combined with hypofractionated radiotherapy (RT) and to develop biomarkers of tumor perfusion and radiosensitization for this combinatorial approach. Experimental Design: Ten patients with T3-4 N0-2 M1 rectal cancer received 7 days of oral nelfinavir (1,250 mg b.i.d.) and a further 7 days of nelfinavir during pelvic RT (25 Gy/5 fractions/7 days). Perfusion CT (p-CT) and DCE-MRI scans were performed pretreatment, after 7 days of nelfinavir and prior to the last fraction of RT. Biopsies taken pretreatment and 7 days after the last fraction of RT were analyzed for tumor cell density (TCD). Results: There were 3 drug-related grade 3 adverse events: diarrhea, rash, and lymphopenia. On DCE-MRI, there was a mean 42% increase in median Ktrans, and a corresponding median 30% increase in mean blood flow on p-CT during RT in combination with nelfinavir. Median TCD decreased from 24.3% at baseline to 9.2% in biopsies taken 7 days after RT (P = 0.01). Overall, 5 of 9 evaluable patients exhibited good tumor regression on MRI assessed by tumor regression grade (mrTRG). Conclusions: This is the first study to evaluate nelfinavir in combination with RT without concurrent chemotherapy. It has shown that nelfinavir-RT is well tolerated and is associated with increased blood flow to rectal tumors. The efficacy of nelfinavir-RT versus RT alone merits clinical evaluation, including measurement of tumor blood flow.
CRIS-Team Scopus Importer:2023-03-08